Delirium and Anesthesia Procedure in Children: A Narrative Literature Review - Yuni Dwi Marantika (HM Publisher, 2021)
A child has a higher risk of perioperative adverse events leading to increased morbidity and mortality. The incidence of delirium is two to three times more common in children than in adults. This review aimed to describe the delirium anesthesia procedure in children. Known risk factors of perioperative anesthesia, such as age, comorbidity, and physical status of the child, have confirmed and identified other risk factors. Respiratory problems during anesthesia, such as severe laryngospasm and bronchospasm, are also more common in children. Emergence delirium (ED) is a challenging phenomenon for those focusing on the pathophysiology of this complication. Delirium in hospitalized children is characterized as hypoactive, hyperactive, or mixed. Signs of delirium can be difficult to detect and categorize in a critically ill child for many reasons, including the child’s developmental level and the overlapping of the indications of delirium with signs and symptoms associated with pain, sedation, and opioid withdrawal. In conclusion, preventive strategies for delirium in children rely on preventing preoperative anxiety, treating postoperative pain, and administering propofol at the end of the surgery, intraoperative dexmedetomidine, and dexamethasone. When occurring, parents should be informed about the possible postoperative maladaptive behaviors in weeks or months following surgery.